2020
DOI: 10.1016/j.heliyon.2020.e04743
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology of coronaviruses: current knowledge

Abstract: The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) late December 2019 in Wuhan, China, marked the third introduction of a highly pathogenic coronavirus into the human population in the twenty-first century. The constant spillover of coronaviruses from natural hosts to humans has been linked to human activities and other factors. The seriousness of this infection and the lack of effective, licensed countermeasures clearly underscore the need of more detailed and comprehensive unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 143 publications
(352 reference statements)
0
108
0
Order By: Relevance
“…Mouse hepatitis coronavirus spike protein localizes in the endoplasmic reticulum-Golgi intermediate compartment (ERGIC) in a membrane (M) protein dependent manner. In contrast, when expressed by itself, the spike had a faint reticular appearance (Artika, Dewantari, & Wiyatno, 2020; Opstelten, Raamsman, Wolfs, Horzinek, & Rottier, 1995).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Mouse hepatitis coronavirus spike protein localizes in the endoplasmic reticulum-Golgi intermediate compartment (ERGIC) in a membrane (M) protein dependent manner. In contrast, when expressed by itself, the spike had a faint reticular appearance (Artika, Dewantari, & Wiyatno, 2020; Opstelten, Raamsman, Wolfs, Horzinek, & Rottier, 1995).…”
Section: Resultsmentioning
confidence: 95%
“…Emerging SARS-CoV-2 is a global public health threat to society, which is predicted to be long-term for several years (Kissler, Tedijanto, Goldstein, Grad, & Lipsitch, 2020). Although there are multiple ongoing endeavors to develop neutralizing antibodies, vaccines, and drugs against the virus (Callaway, 2020; Riva et al, 2020), the lack of adequate, licensed countermeasures underscores the need for a more detailed and comprehensive understanding of the molecular mechanisms underlying the pathogenesis of the virus (Artika et al, 2020). Fundamental knowledge has significant implications for developing countermeasures against the virus, including diagnosis, vaccine design, and drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging SARS-CoV-2 is a global public health threat to society, which is predicted to be long-term for several years ( 44 ). Although there are multiple ongoing endeavors to develop neutralizing antibodies, vaccines, and drugs against the virus ( 45 , 46 ), the lack of adequate, licensed countermeasures underscores the need for a more detailed and comprehensive understanding of the molecular mechanisms underlying the pathogenesis of the virus ( 47 ). Fundamental knowledge has significant implications for developing countermeasures against the virus, including diagnosis, vaccine design, and drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the SARS-CoV structural proteins have been reported to interact with each other and play an essential role in virus assembly [6,15,28]. Therefore, in this study, we report the intraviral PPI among structural proteins of SARS-CoV-2, where we have computationally shown that the M proteins interact with other structural proteins to form complexes of M-E, M-S, and M-N, which responsible for the proper virus assembly.…”
Section: Discussionmentioning
confidence: 99%